Evaluation of Formalin-Inactivated Vaccine Efficacy against Red Seabream Iridovirus (RSIV) in Laboratory and Field Conditions - Joon-Gyu Min; Guk-Hyun Kim; Chong-Han Kim; Woo-Ju Kwon; Hyun-Do Jeong; Kwang-Il Kim (Vaccines, 2024)
Red seabream iridovirus (RSIV) is a major cause of marine fish mortality in Korea, with no effective vaccine available since its first occurrence in the 1990s. This study evaluated the efficacy of a formalin-killed vaccine against RSIV in rock bream under laboratory and field conditions. For the field trial, a total of 103,200 rock bream from two commercial marine cage-cultured farms in Southern Korea were vaccinated. Farm A vaccinated 31,100 fish in July 2020 and monitored them for 18 weeks, while farm B vaccinated 30,700 fish in August 2020 and monitored them for 12 weeks. At farm A, where there was no RSIV infection, the vaccine efficacy was assessed in the lab, showing a relative percentage of survival (RPS) ranging from 40% to 80%. At farm B, where natural RSIV infections occurred, cumulative mortality rates were 36.43% in the vaccinated group and 80.32% in the control group, resulting in an RPS of 54.67%. The RSIV-infectious status and neutralizing antibody titers in serum mirrored the cumulative mortality results. This study demonstrates that the formalin-killed vaccine effectively prevents RSIV in cage-cultured rock bream under both laboratory and field conditions.